2005
DOI: 10.2139/ssrn.986365
|View full text |Cite
|
Sign up to set email alerts
|

Does Sports Performance Influence Revenues and Economic Results in Spanish Football?

Abstract: English football began taking steps towards becoming a business earlier than Spanish football did, and academic studies on the football industry to date also focus primarily on football in the UK. The evidence for the relationship between sports performance and revenues appear clear in English football. There is even research about the effects of a club's wealth on its sports performance, or the effects of a club's sporting situations on its finances. In this paper, we analyse the relationship between sports p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 16 publications
0
32
2
Order By: Relevance
“…186-193) demonstrate that the revenues of English clubs are largely determined by league position, while Bernile and Lyandres (2008) found that winning European Champions League and UEFA Cup games has a positive effect on a club's return on assets. Barajas, Fernandez-Jardon and Crolley (2007) show that for Spanish football clubs, success on the pitch has a positive effect on club revenues. In addition, Pinnuck and Potter (2006) discovered that match day receipts, membership receipts, sponsorship and other marketing receipts for the Australian Football League are a positive function of winning games.…”
mentioning
confidence: 88%
“…186-193) demonstrate that the revenues of English clubs are largely determined by league position, while Bernile and Lyandres (2008) found that winning European Champions League and UEFA Cup games has a positive effect on a club's return on assets. Barajas, Fernandez-Jardon and Crolley (2007) show that for Spanish football clubs, success on the pitch has a positive effect on club revenues. In addition, Pinnuck and Potter (2006) discovered that match day receipts, membership receipts, sponsorship and other marketing receipts for the Australian Football League are a positive function of winning games.…”
mentioning
confidence: 88%
“…In order to get rid of the inverse relationship between UEFA ranking and performance, we assign the following relative ranking to league (Barajas, Fernández-Jardón and Crolley, 2005):…”
Section: Variables and Datamentioning
confidence: 99%
“…The rationale for this choice is based on the assumption that on-pitch performance is a primary driver of football club revenues. Empirical evidence for this assumption has been found by Szymanski and Kuypers (1999), Deloitte and Touche (1999;2000a;2000b), and Barajas, Fernández-Jardón, and Crolley (2005). These are not, however, the only studies assuming clubs' revenues as a function of sporting performance, both under an explicit exclusive context or in combination with other factors.…”
Section: Research Methodology the Dependent Variablementioning
confidence: 99%
“…Specifically, we measure on-pitch performance by the number of competition points gained at the end of each sporting season by our population of football clubs in their domestic league (Serie A). As Barajas et al (2005) pointed out, this is an appropriate measure of sporting performance, when dealing with open-league competitions. An alternative measure, which is oft-used in US-based studies of (team) sports economics, is the winning percentages, computed as the ratio of games won to the total number of games played during the season.…”
Section: Research Methodology the Dependent Variablementioning
confidence: 99%